Reversal of morphine tolerance by a compound with NPFF receptor subtype-selective actions. (1st January 2015) - Malin, David H.; Henceroth, Mallori M.; Izygon, Jonathan J.; Nghiem, Duyen M.; Moon, Will D.; Anderson, Andrea P.; Madison, Caitlin A.; Goyarzu, Pilar; Ma, Jian-Nong; Burstein, Ethan S.
Highlights: AC-263093 previously activated type 2, but not type 1, Neuropeptide FF receptors. Morphine infusion induced robust tolerance to morphine analgesia (tail flick test). AC-263093, 10 mg/kg i.p., totally reversed this tolerance to 5 mg morphine sulfate. AC-263093 did not induce an analgesic effect in rats never exposed to morphine. AC-263093 blocked activation of type 1 receptor, further altering balance between types 1 and 2. Abstract: Neuropeptide FF (NPFF) modulates opiate actions. It has pro-nociceptive effects, primarily through the NPFF receptor 1 subtype, and anti-nociceptive effects, primarily through the NPFFR2 subtype. AC-263093 is a small l, organic, systemically active molecule that was previously shown to functionally activate NPFFR2, but not NPFFR1. It was hypothesized that AC-263093 would attenuate morphine tolerance. Rats were tested for radiant heat tail-flick latency before and after 5 mg/kg morphine sulfate s.c. They were then rendered morphine-tolerant by continuous subcutaneous infusion of 17.52 mg/kg/day morphine sulfate. On the seventh day of infusion, they were retested for analgesia 10 and 20 min after 5 mg/kg morphine sulfate s.c. Tolerance was indicated by reduction of morphine analgesia from the pre-infusion test. Fifty minutes prior to morphine challenge, rats received either 10 mg/kg i.p. AC-263093 or injection vehicle alone. AC-2623093-treated rats had far smaller tolerance scores than control rats. This drug effect was significant, p  = 0.015. The same dose of AC-263093 had almost no analgesic effect in non-tolerant, saline-infused rats. In vitro experiments revealed that AC-263093 had equal affinity for NPFFR1 and NPFFR2, and functionally inactivated NPFFR1, in addition to its previously shown ability to activate NPFFR2. Thus, altering the balance between activation of NPFF receptor subtypes may provide one approach to reversing opiate tolerance.